Effectiveness of animal-assisted activities and therapies for autism spectrum disorder: a systematic review and meta-analysis - Xiao, Ningkun; Bagayi, Vaishnavi; Yang, Dandan; Huang, Xinlin; Zhong, Lei; Kiselev, Sergey; Bolkov, Mikhail A.; Tuzankina, Irina A.; Chereshnev, Valery A. (Frontiers in Veterinary Science, 2024)
Background: Given the rising interest in complementary therapeutic strategies for autism spectrum disorder (ASD), this research aims to provide a comprehensive analysis of the impact of animal-assisted activities and therapies (AAAT) on various ASD symptoms.Methods: A meticulous search of databases, including Scopus and PubMed, was conducted to gather relevant research on AAAT for ASD. This process led to the selection of 45 studies encompassing 1,212 participants. The chosen studies were then subjected to a meta-analysis to evaluate the efficacy of AAAT in alleviating core ASD symptoms.Results: The meta-analysis revealed significant improvements in several core ASD symptoms due to AAAT. Notably, there were improvements in social communication (MD = -4.96, 95% CI [-7.49, -2.44], irritability (MD = -2.38, 95% CI [-4.06, -0.71]), hyperactivity (MD = -4.03, 95% CI [-6.17, -1.89]), and different word usage skills (MD = 20.48, 95% CI [7.41, 33.55]). However, social awareness (MD = -1.63, 95% CI [-4.07, 0.81]), social cognition (MD = -3.60, 95% CI [-9.36, 2.17]), social mannerisms (MD = -0.73, 95% CI [-2.55, 1.09]), social motivation (MD = -1.21, 95% CI [-2.56, 0.13]), lethargy (MD = -1.12, 95% CI [-3.92, 1.68]), and stereotypical behaviors (MD = -0.23, 95% CI [-1.27, 0.80]) did not significantly improve.Conclusions: The study demonstrates the potential of AAAT in improving certain core symptoms of ASD, such as social communication, irritability, hyperactivity, and word usage skills. However, the effectiveness of AAAT in other ASD symptom domains remains uncertain. The research is limited by the absence of long-term follow-up data and a high risk of bias in existing studies. Therefore, while the findings indicate the promise of AAAT in specific areas, caution is advised in generalizing its efficacy across all ASD symptoms.